Implementasi Program Dana Desa (DD) di Desa Tote Kecamatan Bolangitang Barat Kabupaten Bolaang Mongondow Utara - Kelfin Dulung; Ismet Sulila; Yacob Noho Nani (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
This study aims to analyze the implementation of the Village Fund (Dana Desa/DD) Program in Tote Village, Bolangitang Barat Subdistrict, North Bolaang Mongondow Regency. The study focuses on the implementation of the Village Fund policy as viewed from several aspects, namely (a) organizational capacity, (b) information dissemination, (c) community support, and (d) the distribution of village potential This study employed a qualitative, descriptive research approach Data sources were obtained through in-depth interviews with village officials and community members, supported by observation and documentation The results showed that the implementation of the Village Fund Program in Tote Village has not been fully optimal This is indicated by the lunited organizational capacity of village apparatus, uneven dissemination of information to the community, and relatively low community participation and support in several Village Fund programs. In addition, the distribution of village potential in program implementation has not been entirely well-targeted. Nevertheless, the Village Fund Program has contributed positively to infrastructure development and the economic empowerinent of the village community. It can be concluded that improving the implementation of the Village Fund Program requires strengthening village officials capacity, enhancing transparency and information dissemination, and actively involving the community in the planning, implementation, and supervision of the program.